The influence of hospital servicescapes on patient loyalty mediated by patients’ emotion and satisfaction: A study at private hospital in Indonesia - Illona Andromeda, M.D.; Ferdi Antonio, M.D., Ph.D. (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. This study aims to analyze the influence of hospital servicescape towards patient loyalty mediated by patient emotion and patient satisfaction. The research model made based on the adoption of previous study in a healthcare facility, which was empirically tested on patients in a cardiovascular outpatient setting at a private hospital in Jakarta, Indonesia. Data was taken through a simple random sampling, with 162 eligible respondents. Data from respondents were derived through questionnaires using a Likert scale which was distributed online during September 2021 and analyzed using PLS-SEM. Results of this study showed that hospital servicescape has significant influence on mediating variables, namely patient emotion and patient satisfaction. Positive significant relationship was found on positive emotion, which appeared to have the strongest influence towards dependent variable. These findings confirmed the management theory based on servicescape, which had become one of the appealing topics especially with its relation in the healthcare industry.Abstrak. Penelitian ini bertujuan untuk menganalisis pengaruh servicescape rumah sakit terhadap loyalitas pasien yang dimediasi oleh emosi pasien dan kepuasan pasien. Model penelitian dibuat berdasarkan adopsi penelitian sebelumnya di fasilitas kesehatan, yang diuji secara empiris pada pasien dalam pengaturan rawat jalan kardiovaskular di sebuah rumah sakit swasta di Jakarta, Indonesia. Pengambilan data dilakukan secara simple random sampling, dengan jumlah responden yang memenuhi syarat sebanyak 162 orang. Data dari responden diperoleh melalui kuesioner dengan menggunakan skala Likert yang disebarkan secara online selama bulan September 2021 dan dianalisis menggunakan PLS-SEM. Hasil penelitian ini menunjukkan bahwa servicescape rumah sakit berpengaruh signifikan terhadap variabel mediasi; yaitu emosi pasien dan kepuasan pasien. Hubungan signifikan positif ditemukan pada emosi positif, yang tampaknya memiliki pengaruh paling kuat terhadap variabel dependen. Temuan ini menegaskan teori manajemen berbasis servicescape, yang telah menjadi salah satu topik menarik terutama dalam kaitannya dengan industri kesehatan. Model penelitian ini memiliki akurasi prediksi yang besar sehingga dapat dikembangkan untuk penelitian lebih lanjut.